2022
DOI: 10.7860/njlm/2022/51168.2604
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immature Platelet Fraction in Patients with Fever and Thrombocytopenia and its Clinical Utility

Abstract: Introduction: Thrombocytopenia is very common in dengue and other haematological disorders and the aetiology is multifactorial. Immature Platelet Fraction (IPF) is a novel parameter which is a measure of reticulated platelets and it reflects the rate of regeneration of platelets. Aim: To evaluate the relationship between the IPF and platelet recovery and the consistency of its expression. Materials and Methods: The present study was a retrospective observational study done at Institute of Pathology, Madras M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other studies show that the usual reference range for IPF is between 1.6 and 7.1% in adults, while in children, it is between 1.0 and 6.8% [11]. Several studies reported that IPF >10% predicted platelet recovery within 48-72 hours [2,7]. The IPF will start to decrease the following day after reaching its peak value.…”
Section: Immature Platelet Fractionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies show that the usual reference range for IPF is between 1.6 and 7.1% in adults, while in children, it is between 1.0 and 6.8% [11]. Several studies reported that IPF >10% predicted platelet recovery within 48-72 hours [2,7]. The IPF will start to decrease the following day after reaching its peak value.…”
Section: Immature Platelet Fractionmentioning
confidence: 98%
“…However, prophylactic platelet transfusion for severe thrombocytopenia in hemodynamically stable patients has been demonstrated to be ineffective and unnecessary, according to WHO. To prevent unnecessary platelet transfusions, doctors can use IPF to predict platelet recovery in dengue fever patients [7].…”
Section: Immature Platelet Fractionmentioning
confidence: 99%
See 1 more Smart Citation